Business Strategy to Serve Secondary Market for Premium Medical Devices Business in Indonesia (Project East Java-XYZ Company, "A" Division) - Bombong, Andreas V; Toha, Mohamad; Wicaksono, Agung (The Indonesian Journal of Business Administration, 2012)
The project is to formulize business strategy for â€œAâ€ Division to maximize its presence and market share in Secondary Market.Â  The target is to have annual sales of 6 billion rupiah from one projected area only and touch 90% of total healthcare facilities in the area.Â  The Project started from determining desired Area, Key Success Factors, Implementation Plans, Activity Plan, and budget feasibility. The result of data processing combined in business model is the company need to expand to East Java, have business representative in every city of the area, build strong brand identity through training and education to Healthcare Professional, reduce price list in order to be more competitive, and build strategic partnership with Ministry of Health and other professional Infection Organization.Â  From above strategic plans, the project should manage to reach its target .Â The conclusion is that Secondary Market has big potential that in return will benefit the company if treated correctly. East Java project alone would be able to contribute around 15% of national target for â€œAâ€ Division in the next 5 years.Â  Recommendation: XYZ to start the project in other potential area like North Sumatera, West and Central Java, South and North Sulawesi, East Kalimantan, and East Indonesia, with Surabaya as the hub of distribution.Â  Further studies regarding local production should be done by XYZ Medical Indonesia to have a better competition landscape in the market, as well as better reception by the policy makers as the product will have high local content. Keywords: Medical Devices, Business Strategy, Business Model, East Java